Multigenerational downregulation of insulin/IGF‐1 signaling in adulthood improves lineage survival, reproduction, and fitness in Caenorhabditis elegans supporting the developmental theory of ageing. (1st December 2022) - Duxbury, Elizabeth M. L.; Carlsson, Hanne; Sales, Kris; Sultanova, Zahida; Immler, Simone; Chapman, Tracey; Maklakov, Alexei A.
Abstract: Adulthood‐only downregulation of insulin/IGF‐1 signaling (IIS), an evolutionarily conserved pathway regulating resource allocation between somatic maintenance and reproduction, increases life span without fecundity cost in the nematode, Caenorhabditis elegans . However, long‐term multigenerational effects of reduced IIS remain unexplored and are proposed to carry costs for offspring quality. To test this hypothesis, we ran a mutation accumulation (MA) experiment and downregulated IIS in half of the 400 MA lines by silencing daf‐2 gene expression using RNA interference (RNAi) across 40 generations. Contrary to the prediction, adulthood‐only daf‐2 RNAi reduced extinction of MA lines both under UV‐induced and spontaneous MA. Fitness of the surviving UV‐induced MA lines was higher under daf‐2 RNAi. Reduced IIS increased intergenerational F1 offspring fitness under UV stress but had no quantifiable transgenerational effects. Functional hrde‐1 was required for the benefits of multigenerational daf‐2 RNAi. Overall, we found net benefit to fitness from multigenerational reduction of IIS and the benefits became more apparent under stress. Because reduced daf‐2 expression during development carries fitness costs, we suggest that our findings are best explained by the developmental theory of ageing, which maintains that the decline in the force of selection with age results in poorly regulated gene expression in adulthood.